Piezoelectric properties of Mg doped ZnO thin film using sol-gel method and spin coating - Ab Sukor, N. S.; Sutjipto, A. G. E.; Shaitir, A.; Mohamad Ashry, Jusoh (Universiti Malaysia Pahang, 2021)
This reports about the synthesis of Mg doped ZnO thin film using spin-coating techniques through sol-gel method. For studying piezoelectric properties, optical properties and morphology, the prepared Mg doped ZnO thin film samples were characterized using Ultraviolet-Visible Spectroscopy (UV-Vis), Photoluminescence Spectroscopy (PL), X-ray Diffraction (XRD), Field Emission Scanning Electron Microscope (FESEM) and Ultrasonic Vibrator. The particle size was evaluated using Scherrer’s formula from XRD patterns. The results show the crystallite size decreased with increasing Mg concentrations. The optical properties showed that sample exhibit a blue shift in absorption in UV spectra indicating good optical properties. The morphology of grain size microstructure was observed from FESEM with results the grain size of the samples decreased with increasing Mg doping. The piezoelectric properties were evaluated using ultrasonic vibrator and multimeter to obtain potential difference for each sample. The results obtained that potential difference increase with increasing Mg contents and higher rotation of spin speed was used.